Pemberdayaan Perempuan dalam Pengembangan Ekonomi Lokal di Padukuhan Mojosari Desa Monggol Kecamatan Saptosari Kabupaten Gunung Kidul - Siti Nur Azizah; Dinik Fitri Rahajeng Pangestuti (Politeknik Piksi Ganesha Indonesia, 2022)
Gender inequality is still relatively high. One of the reasons is that the productivity of village women is still an unresolved problem. The purpose of this Community based research (CBR) is to obtain an overview of their potential and the problems faced by women who carry out economic activities. Padukuhan Mojosari is an area that has abundant cassava, corn and fertile farms and has the potential for independence and entrepreneurship. However, these results are not maximized because most need a clear market share. This CBR uses the WESD (Woman Education for Sustainable Development) method, a learning method for women in sustainable development, by providing awareness of an innovative and creative entrepreneurial spirit. The outcome of this CBR is the growth of an entrepreneurial spirit that is independent, innovative, and empowered by women with increased ability, knowledge and skills in processing food made from cassava and corn in collaboration with local SMEs. Moreover, the farmer's family has animal feed without buying it..